Differential Rotation and Turbulence in Extended HI Disks - Sellwood, J; Balbus, S (1998)
When present, extended disks of neutral hydrogen around spiral galaxies show a remarkably uniform velocity dispersion of approx 6 km/s. Since stellar winds and supernovae are largely absent in such regions, neither the magnitude nor the constancy of this number can be accounted for in the classical picture in which interstellar turbulence is driven by stellar energy sources. Here we suggest that magnetic fields with strengths of a few microgauss in these extended disks allow energy to be extracted from galactic differential rotation through MHD driven turbulence. The magnitude and constancy of the observed velocity dispersion may be understood if its value is Alfvenic. Moreover, by providing a simple explanation for a lower bound to the gaseous velocity fluctuations, MHD processes may account for the sharp outer edge to star formation in galaxy disks.